CENTENARIANS IN EUROPE - Teixeira, L. (Innov Aging, 2017)
In the last decade, the number of centenarians worldwide has increased. Following this tendency, the number of centenarian studies has also exponentially augmented. Given the complexity to conduct research with centenarians, elementary information on this specific age group remains unknown at a European level. This paper compares basic characteristics of centenarians from 32 European countries based on Census 2011. Results revealed that France is the country with higher ratio of centenarians, followed by Italy and Greece; on the other hand Croatia, Romania and Bulgaria present the lower ratio. The distribution according to gender is similar for all countries, with higher ratio of women reaching 100 years old. Different patterns of education level were found on countries where this information was reliable: Portugal and Greece are the countries with lower levels of education, with more than half without formal education; Finland, UK and Iceland are the countries with higher levels of education, with all centenarians having at least lower secondary education. Analysing the residence situation (living in the community or living in the institution), Romania, Bulgaria, Lithuania, Greece and Latvia are the countries that present higher percentages of centenarians living in the community; Iceland is the country with lower percentage of centenarians living in the community. A positive correlation between the number of centenarians and the percentage of Total Health Expenditure of GDP is observed. This study provides important information about the current profile of European centenarians, which is compared to general information on the centenarian population from EUA and Asia.